Interrater Variability among Anaesthesiologists Using American Society of Anesthesiologists Physical Status Classification System - Sharma Bhattarai, Amit; Bista, Navindra Raj; Basnet, Madindra Bahadur; Joshi, Deepak Raj; Shrestha, Anil (Journal of Nepal Health Research Council, 2024)
Background: The American Society of Anaesthesiologists Physical Status classification is deployed by the anaesthesiologists worldwide to classify operative surgical patients. Many studies have found moderate degree of interrater variability among anaesthesiologists. The general objective of the study was to find out interrater variability among Nepalese anesthesiologists using this classification system in Nepal. The specific objectives of the study were to find out the correctness of assignment and inter-rater variability among anaesthesiologists based on their experience. Methods: Ten clinical cases were distributed among 130 registered anaesthesiologist practitioners of Nepal after validation with the experts. Respondents were asked to assign each of ten cases to a specific physical status class. Anaesthesiologists were classified to two classes based on clinical experience as having more or less than five years of experience. Results: We found substantial agreement among < 5 year’s (0.66) and > 5 year’s experience group (0.753) and among all raters (0.736). The mean score of the group with less than 5 years of experience was more. There was no significant difference between the mean score (p = 0.595). Overall mean score for the both groups was 5.66 with SD 1.66. There was no significant difference between the groups. Conclusions: The study shows that there is very less variation among registered practising anaesthesiologists of Nepal using American Society of Anesthesiologists Physical Status classification system. Keywords: ASA-PS; interrater; variability.